The sustainable productivity of farmers can be realized if farmers own self relience. Farmers’s self relience can be realized if farmers own capacity to optimize self capacity and utilization of agriculture resources capacity. Through multistage cluster sampling technique, found 75 person as farmer’s sample. Research data including primary data and secondary data. Analysis of data done with correlation test, regression test and path analysis. The conclusion of this research is the self relia - Marliati .; Sumardjo .; Pang S. Asngari; Prabowo Tjitropranoto; Asep Saefuddin (Forum Pasca Sarjana, 2010)
The sustainable productivity of farmers can be realized if farmers own self relience. Farmers’s self relience can be realized if farmers own capacity to optimize self capacity and utilization of agriculture resources capacity.  Through multistage cluster sampling technique, found 75 person as farmer’s sample. Research  data including primary data and secondary data. Analysis of data done  with correlation test, regression test and path analysis.  The conclusion of this research is the self reliance level in agribusiness of food crop farmers, including the category low.  The low level of self reliance of farmers in agribusiness caused by (a) the low level of capacity development needs of farmers in agribusiness, which include low development needs: productivity capacity; marketing capacity; capacity of the security business/agribusiness; capacity in group management; networking capacity and the capacity in performance improvement/progress; (b) low level of performance of agricultural extension; (c) low levels of non-formal education of farmers.   Key words: agriculture extension worker, empowerment, capacity development, self-reliance, agribusiness